Motif Tato Sebagai Ide Penciptaan Seni Grafis - Savana Biru; Dyah Yuni Kurniawati (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The creative work in graphic art is grounded in the rapid development of graphic art as a branch of visual art that continues to advance in both technical execution and visual approach. The growth of printing technologies both manual and digital has opened up broader opportunities for the realization of visual concepts rooted in diverse cultural traditions. One such rich visual and symbolic source is Japanese tattoo art (Irezumi), which historically and philosophically embodies values such as courage, resilience, harmony, and the cycle of life and death. Motifs such as koi fish, dragons, cherry blossoms, and phoenixes are characterized by bold outlines, soft gradients, and dense compositions, making them highly adaptable to the medium of graphic art. The objective of this creative project is to explain the visual characteristics and symbolic meanings of Japanese tattoo motifs as the conceptual basis for the creation of two-dimensional graphic artworks; to apply their aesthetic and philosophical values within a contemporary visual context; and to implement these motifs using appropriate visual strategies and printing techniques. The creative process involved digital design methods and the use of Direct to Film (DTF) printing technology on fabric media, enabling accurate and practical visual application. Theoretical studies supporting this work include analyses of Japanese tattoo symbolism, principles of graphic design, and the cultural values underlying the selection and adaptation of these motifs. The resulting works, including Up and Down and Dragon and Tiger, present visual interpretations of life’s dualities and the balance between spiritual and worldly forces. The outcomes demonstrate that the implementation of Japanese tattoo motifs in graphic art not only enriches contemporary visual expression but also serves as a medium for preserving and recontextualizing traditional cultural values in a relevant and meaningful visual form